(untitled) (Research, Society and Development, 2025)
This study aims to analyze the historical evolution of Brazilian legislation addressing bullying in the school context, highlighting the relationship between these regulations and children’s and adolescents’ rights. The research question guiding the investigation was: how have Brazilian laws approached and evolved in combating bullying in schools over time? The methodology adopted was qualitative and descriptive, based on a bibliographic and documentary review. The research involved the analysis of primary and secondary sources, including legislation and other educational regulations. Additionally, international treaties were examined. The results revealed a gradual evolution of Brazilian legislation in combating school bullying, with emphasis on the strengthening of public policies and the creation of legal frameworks, such as Law No. 14,811/2024, which criminalizes bullying and cyberbullying. The research contributes to understanding the importance of legislation as a tool for promoting a safe and inclusive school environment.